Industry Funding of Oncology Randomised Controlled Trials: Implications for Design, Results and Interpretation. Issue 1 (January 2022) - Fundytus, A.; Wells, J.C.; Sharma, S.; Hopman, W.M.; Del Paggio, J.C.; Gyawali, B.; Mukherji, D.; Hammad, N.; Pramesh, C.S.; Aggarwal, A.; Sullivan, R.; Booth, C.M.
Abstract: Aims: Most randomised controlled trials (RCTs) in oncology are now funded by the pharmaceutical industry. We explore the extent to which RCT design, results and interpretation differ between industry-funded and non-industry-funded RCTs. Materials and methods: In this cross-sectional analysis, a structured literature search was used to identify all oncology RCTs published globally during 2014–2017. Industry funding was identified based on explicit statements in the publication. Descriptive statistics were used to compare elements of trial methodology and output between industry- and non-industry-funded RCTs. Results: The study sample included 694 RCTs; 71% were funded by industry. Industry-funded trials were more likely to test systemic therapy (97% versus 62%; P < 0.001), palliative-intent therapy (71% versus 41%; P < 0.001) and study breast cancer (20% versus 12%; P < 0.001). Industry-funded trials were larger (median sample size 474 versus 375; P < 0.001) and more likely to meet their primary end point (49% versus 41%; P < 0.001). Among positive trials, there were no differences in the magnitude of benefit between industry- and non-industry-funded RCTs. Trials funded by industry were published in journals that had a significantly higher median impact factor (21, interquartile range 7, 28) than non-industry-funded trials (impact factor 12, interquartile range 5, 24; P = 0.005); this persisted when adjusted for whether a trial was positive or negative. Conclusions: The vast majority of oncology RCTs are now funded by industry. Industry-funded trials are larger, more likely to be positive, predominantly test systemic therapies in the palliative setting and are published in higher impact journals than trials without industry support. Highlights: Industry funded trials tested systemic therapy more than Non-Industry funded trials. Industry-funded trials were more likely to study palliative treatment. Industry-funded trials were more likely to meet their primary endpoint. Industry funded trials studied breast cancer more often. No difference in clinical benefit between industry and non industry funded trials